Synthesis and preliminary characterization of Poly(Propylene)Imine hexadecylamine dendrimer (DAB-Am-16) modified with methyl acrylate - Carmo, Devaney Ribeiro do [UNESP]; Silveira, Tayla Fernanda Serantoni da [UNESP]; Laurentiz, Rosângela Silva de [UNESP]; Bicalho, Urquisa Oliveira [UNESP]; Martins, Leandro [UNESP]; Dias Filho, Newton Luiz [UNESP; Paim, Leonardo Lataro [UNESP] (My University, 2013)
This paper describes the reaction of a Poly(propylene)imine hexadecylamine dendrimer (DAB-Am-16) with methyl acrylate. The modified dendrimer obtained (DKMA) was characterized by vibrational spectroscopy, nuclear resonance magnetic (13C), thermogravimetry and scanning electron microscopy. The dielectric properties of DKMA were studied in a temperature range of -40 to 100°C varying the frequency from 10 to 1000 KHz. A relative thermal stability was found for DKMA. The modified dendrimer behaved as an organic insulating (ε' = 5.1). The synthesis performed at basic medium results in a corresponding change in the conformational property of the precursor. The electron microscopy indicated that the dendrimer presented a modified collapsed shape, expected by the proposed route of synthesis. - See more at: http://www.sciencedomain.org/abstract.php?iid=230&id=16&aid=1469#sthash.xeYKG1Y4.dpuf
Keywords: Dendrimer; methyl acrylate; thermal analysis; dielectric properties; synthesis